Developing Comic Material for Teaching Writing in Narrative Text at the Eighth Grade Students of SMP Negeri 3 Kota Serang - Farras Huda; Siti Hikmah; Rosmania Rima (Journal of English Language Studies, 2017)
The research aimed to (1) identify eighth-grade students’ learning needs of writing narrative text at SMP Negeri 3 Kota Serang, and (2) develop appropriate materials for eighth-grade students of SMP Negeri 3 Kota Serang. The subjects of this Research and Development study were students and teacher of SMP Negeri 3 Kota Serang. The research procedure was simplified and modified the steps from Borg and Gall (1983:775) and Jolly and Bolitho (cited in Tomlinson, 1998): conduct the needs analysis, write the course grid, develop the first draft, evaluate by expert judgments, revise, evaluate the second draft, and implement of the material. The data collection instruments were the needs analysis questionnaire, interview, and expert judgment questionnaire, which analyzed through percentage, mean followed by descriptive analysis's conversion and qualitative data analysis. The researchers found that both teacher and students wanted specific writing activities in the form of three units of printed comic material through design the layout and storyboard, sketch the characters, and draw and write the activity. The result of the first evaluation by two expert judgments showed the material was in range “fair”, “good” and “very good” while the second was in range “very good”.  The product offer creativity and interactivity for English teacher and another developer in the future. Keywords: narrative text, writing, comic material